1996
DOI: 10.1002/(sici)1097-4644(199608)62:2<165::aid-jcb4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear matrix as an anchor for protein kinase CK2 nuclear signalling

Abstract: Nuclear matrix (NM) is not only the structural basis for nuclear shape but also is intimately involved in nuclear functional activities. Among the modulatory factors that may affect these diverse activities are the signals that may influence the state or composition of the NM proteins. One such mechanism for altering the functional activity of at least some NM proteins may be the extent of their phosphorylation. Protein kinase CK2 appears to associate with NM and to phosphorylate a number of NM-associated prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…Some of the apoptosis-inducing chemical agents are known to induce DNA damage as an initial step, which is a distinguishing feature from receptor-mediated apoptosis (21-23). Our previous work employing receptor-mediated apoptosis in the prostate epithelial cells has shown a distinct response of NM-associated CK2 such that a rapid loss of CK2 from the NM compartment temporally precedes the appearance of apoptosis (1,9,11,14,15,24). However, no such studies have been reported on the response of the CK2 signal in relation to chemical-mediated apoptosis in cancer cells.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Some of the apoptosis-inducing chemical agents are known to induce DNA damage as an initial step, which is a distinguishing feature from receptor-mediated apoptosis (21-23). Our previous work employing receptor-mediated apoptosis in the prostate epithelial cells has shown a distinct response of NM-associated CK2 such that a rapid loss of CK2 from the NM compartment temporally precedes the appearance of apoptosis (1,9,11,14,15,24). However, no such studies have been reported on the response of the CK2 signal in relation to chemical-mediated apoptosis in cancer cells.…”
supporting
confidence: 63%
“…The association of CK2 in these compartments is profoundly responsive to the status of growth stimuli (1,9,(11)(12)(13). To that end, we have employed androgen action in the prostate epithelial cells that is mediated via the androgen-receptor system as an experimental model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…a These authors made equal contribution. b Present address: Northwestern Health Sciences University, Bloomington, MN both the nuclear and cytoplasmic compartments in the cell, and undergoes dynamic shuttling between various compartments which may relate to its functional activity in those compartments (Ahmed et al, 1993;Ahmed, 1994a, 1994b;Tawfic et al, 1996Tawfic et al, , 1997Guo et al, 1998Guo et al, , 1999aGuo et al, , 1999bAhmed et al, 2000;Faust and Montenarh, 2000). A key feature of CK2 cell biology is that it is essential for cell survival (e.g., Padmanabha et al, 1990), and accordingly, attempts to produce CK2-knockout mice have been unsuccessful (Bouchou et al, 2003).…”
Section: General Characteristics Of Protein Kinase Ck2mentioning
confidence: 79%
“…Regulation of cellular CK2 appears to be complex and various hypotheses have been proposed on this subject (for reviews, see e.g., Allende and Allende, 1995;Ahmed, 1999;Montenarh and Faust, 2000;Pinna, 2002;Filhol et al, 2004;Olsten et al, 2005). To explain some of our data on CK2 responses to altered cell growth, we originally proposed that CK2 undergoes dynamic shuttling between cytoplasm and nucleus and further within the nucleus it undergoes differential distribution depending on the conditions to which the cell is exposed (Ahmed et al, 1993;Ahmed, 1999;Ahmed, 1994a, 1994b;Tawfic et al, 1996Tawfic et al, , 1997Guo et al, 1998Guo et al, , 1999aGuo et al, , 1999bAhmed et al, 2000). Subsequently, it was demonstrated that CK2 translocation can take place to other parts of the cell further reinforcing the notion that dynamic intracellular shuttling of CK2 might represent a key mode of its regulation in the cell in response to diverse signals (Tawfic et al, 1997;Faust and Montenarh, 2000).…”
Section: General Characteristics Of Protein Kinase Ck2mentioning
confidence: 99%